Insights to ligand binding to the monoamine transporters—from homology modeling to LeuBAT and dDAT - Koldsø, Heidi; Grouleff, Julie; Schiøtt, Birgit (Frontiers in Pharmacology, 2015)
Understanding of drug binding to the human biogenic amine transporters is essential to explain the mechanism of action of these pharmaceuticals but more importantly to be able to develop new and improved compounds to be used in the treatment of depression or drug addiction. Until recently no high resolution structure was available of the biogenic amine transporters and homology modeling was a necessity. Various studies have revealed experimentally validated binding modes of numerous ligands to the biogenic amine transporters using homology modeling. Here we examine and discuss the similarities between the binding models of substrates, antidepressants, psychostimulants and anti-abuse drugs in homology models of the human biogenic amine transporters and the recently published crystal structures of the drosophila dopamine transporter and the engineered protein, LeuBAT. The comparison reveals that careful computational modeling combined with experimental data can be utilized to predict binding of molecules to proteins that agree very well with crystal structures.